Correlation of Serum Leptin with Circulating Anti-Helico Bacter Pylori IgG Antibodies in End-Stage Renal Failure Patients on Regular Hemodialysis - Baradaran, M.D. Azar; Nasri, M.D. Hamid (Pakistan Journal of Nutrition, 2005)
Leptin is synthesized mainly by the adipose tissue. Leptin also is detected in gastric chief cells. To consider the association of serum leptin with helicobacter pylori- IgG antibodies as parameters of nutritional status, on a group of hemodialysis patients, serum Leptin and serum helicobacter pylori specific IgG (H. Pylori-IgG) antibody titer were measured. Total patients were 36. In all patients there were a significant positive correlation of serum leptin with BMI and a near significant positive correlation of serum leptin with age. In the diabetic HD group a significant inverse correlation of helicobacter pylori IgG antibody titer and serum leptin was seen. This is the first report of the association of serum leptin with pylori-IgG antibodies in hemodialysis patients which may explain nutritional problems that is frequently seen in diabetic hemodialysis patients .More research is needed regarding the clinical consequences of this association.